2013
DOI: 10.1089/zeb.2012.0815
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Gamma Directly Mediates Developmental Biliary Defects

Abstract: Biliary atresia (BA) is the most common identifiable hepatobiliary disease affecting infants, in which there are defects in intra-and extrahepatic bile ducts and progressive fibrosis. Activation of interferon-gamma (IFNc) appears to be critical in both patients with BA and in rodent models of BA. We have recently reported a zebrafish model of biliary disease that shares features with BA, in which inhibition of DNA methylation leads to intrahepatic biliary defects and activation of IFNc target genes. Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…53 Moreover, DNA hypomethylation in zebrafish induced the interferon gamma signaling pathway, and injecting zebrafish larvae with interferon gamma recapitulated the biliary defects mimicking biliary atresia. 54 This provides a potential pathogenic mechanism for biliary atresia which has been proposed in some pediatric cases to be caused by a viral agent that may trigger an antiviral immune response that destroys the developing biliary tract. 55,56 The hypothesis that an antiviral immune response might cause biliary atresia is supported by the finding that corticosteroids prevent the biliary defect caused by DNA hypomethylation in zebrafish, 53 suggesting that these drugs might be used to treat patients with biliary atresia.…”
Section: Heritable and Developmental Liver Diseasesmentioning
confidence: 99%
“…53 Moreover, DNA hypomethylation in zebrafish induced the interferon gamma signaling pathway, and injecting zebrafish larvae with interferon gamma recapitulated the biliary defects mimicking biliary atresia. 54 This provides a potential pathogenic mechanism for biliary atresia which has been proposed in some pediatric cases to be caused by a viral agent that may trigger an antiviral immune response that destroys the developing biliary tract. 55,56 The hypothesis that an antiviral immune response might cause biliary atresia is supported by the finding that corticosteroids prevent the biliary defect caused by DNA hypomethylation in zebrafish, 53 suggesting that these drugs might be used to treat patients with biliary atresia.…”
Section: Heritable and Developmental Liver Diseasesmentioning
confidence: 99%
“…Relying solely on mechanism-based markers is complicated by the fact that most cases of drug-induced hepatotoxicity are idiosyncratic, and only 30% of instances correlate with cause in the national registry (Alfirevic and Pirmohamed, 2012). Further, phenotypic linking of gene expression signatures could identify novel molecular mechanisms linked to drug-induced toxicity and improve the fidelity of biomarker-based diagnostic assays (Cui et al, 2013).…”
Section: Bioinformatics-based Database Mining Of Public Data Repositomentioning
confidence: 99%
“…Early studies by Farooq et al found that the HDAC inhibitor valproic acid impaired liver development by inhibiting hepatoblast specification and differentiation[71]. Embryonic exposure to 5-azacytidine has a deleterious effect on biliary development due to DNA hypomethylation and stimulation of an interferon-γ mediated inflammatory response[72,73]. Recent work using the mTORC inhibitors Torin1 or rapamycin have revealed a critical role for mTOR signaling in Wnt-mediated liver hyperplasia[74].…”
Section: Introductionmentioning
confidence: 99%